Educating for action: critical literacy for democratic citizenship education - Miranda Dávila, Ana Sofía (2026)
This essay aims to present an approach to the concept of critical literacy as a key element in the formation of critical and participatory citizens, capable of engaging with their environment from the school setting. In pursuing such formation, it is the teacher who must first become aware of their professional and civic role in the classroom, a commitment that must be coherently reflected in their pedagogical practice. Moreover, the essay discusses certain practices of critical literacy in schools that enable students to confront the current panorama of post-truth and hate speech disseminated through the media and social networks. In this way, the role of critical literacy becomes an act of engagement that contributes to strengthening our weakened democracy.